(untitled) (Research, Society and Development, 2020)
The objective of this study was to analyze how the socio-professional relationships between health workers act in the suffering caused by armed conflicts in the context of the Family Health Strategy (ESF). It is an intervention research involving thirteen health professionals at a Family Health Unit located in Rio de Janeiro in a dangerous territory where. Institutional Analysis was used as methodological theoretical reference. The methodology allowed us analyze through the meetings with the group, the contradictions in that context, where violence provided a new type of relationship between workers, increasing ties, trust and affection, minimizing the psychological suffering causeds by the armeds conflicts.